Artificial Intelligence in Healthcare: Current Trends and Future Directions - Shambo Samrat Samajdar; Rupak Chatterjee; Shatavisa Mukherjee; Amit Dey; Bharat Saboo; Jyotirmoy Pal; Shashank Joshi; Nandini Chatterjee (Current Medical Issues)
Artificial intelligence (AI) is a milestone technological advancement that enables computers and machines to simulate human intelligence and problem-solving capabilities. This article serves to give a broad overview of the application of AI in medicine including the current applications and future. AI shows promise in changing the field of medical practice although its practical implications are still in their infancy and need further exploration. However, AI is not without limitations and this article also tries to address them along with suggesting solutions by which AI can advance healthcare for betterment with mass benefit.